2007
DOI: 10.1161/strokeaha.107.485649
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive Surgery for the Treatment of Malignant Infarction of the Middle Cerebral Artery (DESTINY)

Abstract: Background and Purpose-Decompressive surgery (hemicraniectomy) for life-threatening massive cerebral infarction represents a controversial issue in neurocritical care medicine. We report here the 30-day mortality and 6-and 12-month functional outcomes from the DESTINY trial. Methods-DESTINY (ISRCTN01258591) is a prospective, multicenter, randomized, controlled, clinical trial based on a sequential design that used mortality after 30 days as the first end point. When this end point was reached, patient enrollme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
606
2
41

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 795 publications
(666 citation statements)
references
References 34 publications
(32 reference statements)
17
606
2
41
Order By: Relevance
“…Until recently, only case series and nonrandomized case-control studies suggested any benefit of decompressive craniectomy [39][40][41][42][43]. Several recent randomized controlled trials have demonstrated improved survival after decompressive craniectomy in certain stroke populations [6,[44][45][46]. These findings may have been influenced by the "early" timing of craniectomy in their protocols, potentially averting secondary brain damage associated with cerebral edema [47], although the inclusion of patients who may not have truly needed decompression also may have favorably influenced outcome.…”
Section: Osmotherapymentioning
confidence: 99%
“…Until recently, only case series and nonrandomized case-control studies suggested any benefit of decompressive craniectomy [39][40][41][42][43]. Several recent randomized controlled trials have demonstrated improved survival after decompressive craniectomy in certain stroke populations [6,[44][45][46]. These findings may have been influenced by the "early" timing of craniectomy in their protocols, potentially averting secondary brain damage associated with cerebral edema [47], although the inclusion of patients who may not have truly needed decompression also may have favorably influenced outcome.…”
Section: Osmotherapymentioning
confidence: 99%
“…Of the 32 patients randomized, 15 of 17 who had received a hemicraniectomy met their primary endpoint vs 7 of 15 in the nonsurgical group. Although their study sample was small, they also found a better outcome (mRS≤3) in 47% of the surgically treated patients vs 27% in the nonsurgical group [66]. Vahedi et al [68] analyzed the randomized patients from the DECIMAL (38 patients) and DESTINY (32 patients) trials in combination with 23 patients from the HAMLET study (which was not complete at the time of this publication), and published a pooled analysis of 93 patients (ages 18-60 with MCA infarct treated within 48 h).…”
Section: Surgical Therapiesmentioning
confidence: 86%
“…Long-term safety and the role for hemicraniectomy was studied by the recent French DECIMAL [65], German DESTINY [66] and Dutch HAMLET [67] trials; and collectively evaluated by a pooled analysis [68]. The DECIMAL study [65] enrolled 38 patients with malignant middle cerebral artery infarction from 7 stroke centers and randomized them to receive standard medical therapy or hemicraniectomy plus standard medical therapy.…”
Section: Surgical Therapiesmentioning
confidence: 99%
“…The decision for patients over 60 years of age must be individualized: there is great controversy regarding this cut-off point, as some authors describe benefits beyond this age-group 12,15,18,19 , while others report unfavorable outcomes 6,7,8,9 . In the present study, three patients over 60 years of age were included.…”
Section: Discussionmentioning
confidence: 99%
“…In order to clearly define the indication for the surgical treatment and to decrease complications derived from DC in a university hospital in southern Brazil, a specific protocol for DC in the treatment of intracranial hypertension derived from ischemia of the MCA region has been implemented since 2007, in conjunction with the neurology department. Even though studies have demonstrated the efficacy of DC in patients presenting with malignant MCA infarction 5,6,7,8,9,10 , some resistance to its application still exists, particularly regarding the functionality of the patients who survive the acute event.The goals of the present study were to assess the mortality rates from the use of DC in the treatment of patients …”
mentioning
confidence: 99%